1995
DOI: 10.1097/00007890-199505000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Immunosuppressive Drugs on Quality of Life After Renal Transplantation

Abstract: This prospective, randomized study investigates the effect of two immunosuppressive treatment regimens on quality of life after renal transplantation. At 3 months after transplantation, patients treated with cyclosporine (CsA) and prednisone (Pred) were allo cated to either withdrawal of Pred (n=60) or to con version of CsA to azathioprine (Aza) (Aza-Pred, n=60). Quality of life was evaluated just before randomiza tion, and at 6 and 12 months after transplantation using the Sickness Impact Profile (SIP), the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Regarding the important issue of quality of life as an out come measure after renal transplantation, we observed no major differences between the groups, although a tendency for better scores on psychosocial items was found in patients successfully taken off steroids (14).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Regarding the important issue of quality of life as an out come measure after renal transplantation, we observed no major differences between the groups, although a tendency for better scores on psychosocial items was found in patients successfully taken off steroids (14).…”
Section: Discussionmentioning
confidence: 58%
“…With a duration of follow-up of at least 2 years in all patients, this article de scribes the results with emphasis on rejection incidence, graft function, and costs. Detailed data on the effects of both therapies on quality of life (14) and lipid metabolism (15) during the first year after transplantation are published separately.…”
mentioning
confidence: 99%
“…There has been some comparison of the HRQoL of patients taking different immunosuppressive treatment regimens. A small, prospective, randomized study indicated that ciclosporin monotherapy may lead to a higher degree of psychosocial well-being compared with conversion from ciclosporin-prednisolone to azathioprine-prednisolone (10). In another small study, no difference was found between patients given tacrolimus and those receiving ciclosporin in terms of physical and mental HRQoL (11).…”
mentioning
confidence: 99%
“…Physical and psychosocial well-being scores, among patients who have undergone renal transplantation, reach levels comparable to those found in the general population. 7 Surgical complications in renal transplantation can be divided into vascular, urological and general surgical complications such as bleeding, wound infections and even lymphocele formation. 8 These complications can lead to loss of allograft and in severe cases loss of patient's life.…”
Section: Original Articlementioning
confidence: 99%